(untitled) (Fiep Bulletin - online, 2011)
This study aimed to determine the lifestyle and physical activity of employees participating in the Program of Gymnastics at the Rectory / UFAL. This study was regarded as descriptive of the type of case study. Sample were selected for 39 employees of both sexes, in various sectors of the Rector. Was used as a tool for data collection, a questionnaire adapted from Alvarez (2002), with open and closed questions related to lifestyle, quality of work life, health / fitness / exercise, physical activity and the gymnastics program. To create the database was using the Excel program, a public system, and the data analysis used descriptive statistics. According to the results the average age of employees was 34 years + and the majority, 48.73% worked 6-8 hours a day. In relation to physical activities were 25.64% exercise consistently, and 41.03% were physical exercises unsystematic way. As for participation in the activities proposed by the program of Gymnastics, 33.33% participated in stretching frequency of sessions, and 38.46% participated in an unsystematic manner. Regarding the importance of physical activity and its meaning, a part of the sample felt it was important to maintaining and improving health. Through this work showed that the Gymnastics becomes a major sponsor and supporter of quality of life for employees and therefore have a greater motivation and interaction related to physical activity, providing an active lifestyle.